Undergraduate Nursing Student Perceptions of Clinical Training Approaches: A Quasi-Experimental Study. - Hardan-Khalil, Kholoud; Jadalla, Ahlam; Deckers, Cathleen M.; Costa, Christine B. (Nursing Reports, 2025)
Background/Objectives: Undergraduate nursing students report encountering significant challenges when they perform preplanning for clinical days. The literature lacks evidence regarding this educational model for clinical training, yet faculty continue to use it despite the lack of evidence that supports it. This study explored undergraduate nursing students' perceptions of their preclinical training activities. Methods: A quasi-experimental, after-only, nonequivalent control group design was employed at a public nursing school in an urban setting. A total of 110 undergraduate nursing students enrolled in an advanced medical–surgical course. Participants were divided into two groups based on their preparation approach for clinical practice. Data were collected using a paper-and-pencil survey at the end of the course's clinical rotation. The survey comprised three sections: (1) sociodemographic information, (2) the nursing clinical education tool (NCET) developed for this study, and (3) two open-ended questions focusing on the pros and cons of preplanning and reflective care approaches. The responses were analyzed and compared using a nonparametric two-independent-samples Mann–Whitney U test. Results: The findings indicated that students in eight out of ten nursing clinical education survey categories favored the reflective care approach. No differences were found between groups concerning class grade point average (GPA), the National Council Licensure Examination (NCLEX) passing rate, or standardized tests. Conclusions: The reflective care approach was perceived more favorably than preplanning. Engaging in clinical reasoning strategies requires educators to reconsider how students interact with clinical education. Further research is needed to develop evidence-based methods to enhance the clinical learning experience and promote patient safety.